PELEMAHAN KEBIJAKAN PEMERINTAH DAERAH DALAM PEMANFAATAN DAN PENGEMBANGAN TANAH KAS DESA (Studi Kasus di Kalurahan Srimulyo, Kapenewon Piyungan, Kabupaten Bantul, Daerah Istimewa Yogyakarta) - Elsa Pebriani Sinaga; Tri Daya Rini (GOVERNABILITAS (Jurnal Ilmu Pemerintahan Semesta), 2022)
The problem in this research is about the local government policy which limits the authority of the village head in the utilization of Village/Kalurahan treasury land. The question posed in this research is what are the policies and constraints of the village administration in the utilization and development of village treasury land. This research uses qualitative methods with case study studies. Primary data was collected through observation, documentation and in-depth interviews. Secondary data was collected through literature study: documents, journals and books. In analyzing this research, theories and concepts about policy are used, where in general policy is defined as an effort to solve, reduce, and prevent something bad and should be an advocate, innovation, and leader of goodness in the best way and directed action. The findings of this study indicate that local government policies have confined the Srimulyo Village regarding the utilization and development of village treasury land. Utilization of village treasury land cannot be done optimally, because it does not provide added economic value for the Lurah and Kalurahan apparatus.